2006
DOI: 10.1590/s1677-04202006000200004
|View full text |Cite
|
Sign up to set email alerts
|

Use of the QTL approach to the study of soybean trait relationships in two populations of recombinant inbred lines at the F7 and F8 generations

Abstract: This work aimed to identify the quantitative trait loci (QTL) associated with photosynthesis and growth and productivity traits of soybean and to study possible associations between these traits by the analysis of coincidence of QTL in linkage groups (LGs). Thus, populations of recombinant inbred lines (RILs) of the F7 and F8 generations derived from the cross between the varieties BARC-8 and Garimpo were used. The traits evaluated were net assimilation rate of CO2 under saturating light (Asat), potential phot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 20 publications
1
15
0
1
Order By: Relevance
“…Broad-sense heritability values between traits ranged from 44.92 to 86.59%, including medium and high values. Estimates close to those found for the same yield traits are reported in other studies on soybeans (Pooprompan et al 2006, Vieira et al 2006, Kim et al 2012). Higher heritability coefficient was observed for the traits NDM, NNM and W100S, indicating that the phenotypic selection efficiency can be high, since the heritability expresses the proportion of total variance, which is attributed to the genetic variation (Falconer and Mackay 1996).…”
Section: Resultssupporting
confidence: 89%
“…Broad-sense heritability values between traits ranged from 44.92 to 86.59%, including medium and high values. Estimates close to those found for the same yield traits are reported in other studies on soybeans (Pooprompan et al 2006, Vieira et al 2006, Kim et al 2012). Higher heritability coefficient was observed for the traits NDM, NNM and W100S, indicating that the phenotypic selection efficiency can be high, since the heritability expresses the proportion of total variance, which is attributed to the genetic variation (Falconer and Mackay 1996).…”
Section: Resultssupporting
confidence: 89%
“…Using a RIL population derived from soybean varieties BARC-8 and Garimpo, Vieira et al (2006) detected two QTLs for net assimilation rate of CO 2 . These QTLs were located in intervals satt241-satt345 on LG O and satt215-satt183 on LG J, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have investigated the relationships between physiological traits through QTL mapping (Lebreton et al 1995;Quarrie et al 1997;Thumma et al 2001). QTLs for photosynthetic rate (P N ) have been identified in many crops, including sunflower (Herve et al 2001), soybean (Vieira et al 2006), and rice (Teng et al 2004). P N is a final in vivo photosynthetic activity that depends on many traits (parameters).…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies on mapping quantitative trait loci (QTL) have published for soybean in the experimental crosses (e.g., Mansur et al 1993;Lee et al 1996a, b, c;Concibido et al 2004;Vieira et al 2006;Guzman et al 2007), but no report in the pedigree has been found. Grupe et al (2001) propose in silico QTL-mapping method for analyzing the pedigree data and identify Jun Qin and RunQing Yang contributed equally to this work.…”
Section: Introductionmentioning
confidence: 99%